How to manage patients with germline DDX41 variants: Recommendations from the Nordic working group on germline predisposition for myeloid neoplasms - Panagiotis Baliakas; Bianca Tesi; Jörg Cammenga; Asbjørg Stray‐Pedersen; Kirsi Jahnukainen; Mette Klarskov Andersen; Helena Ågerstam; Maria Creignou; Ingunn Dybedal; Klas Raaschou‐Jensen; Kirsten Grønbæk; Outi Kilpivaara; et al. (HemaSphere, 2024)
Abstract Increasing recognition of germline DDX41 variants in patients with hematological malignancies prompted us to provide DDX41‐specific recommendations for diagnosis, surveillance, and treatment. Causative germline variants in the DDX41 predispose to the development of myeloid neoplasms (MNs), especially myelodysplastic syndrome (MDS) and acute myeloid leukemia (AML). Almost 3%–5% of all patients with MDS or AML carry a pathogenic or likely pathogenic germline DDX41 variant, while half of them acquire a somatic second hit in the other allele. DDX41‐associated MNs exhibit unique clinical characteristics compared to other hematological malignancies with germline predisposition: MNs occur mostly at advanced age and follow an indolent clinical course. Male carriers are more prone to develop MDS or AML than females. DDX41‐associated MN is often hypoplastic, and the malignancy may be preceded by cytopenias.